Induction of adipose tissue regeneration by chemically-modified hyaluronic acid. (28th January 2008) - Rhodes, Nicholas P.; Di Bartolo, Chiara; Bellini, Davide; Hunt, John A.
Hyaluronan was modified by amidation of the carboxyl groups with dodycyl amides to produce a viscous gel (HYADD3). Small aliquots were implanted intramuscularly in Wistar rats at a concentration of 30 mg/ml for up to 12 weeks. Standard histology and immunohistochemistry demonstrated low levels of inflammation at all time periods, absence of any fibrous capsule coupled with the presence of mature adipocytes within the degrading gel. It is concluded that the chemical architecture of HYADD3 gel causes the de novo regeneration of soft tissue by recruitment of appropriate progenitor cells.